MULTICOMPONENT DIFFUSION AND CONVECTION IN MOLTEN MGO-AL2O3-SIO2 - Richter F.M.; Yan L.; Minarik W.G. (My University, 1998)
Multicomponent diffusion and convection in molten MgO-Al2O3-SiO2 at 1550°C and 0.5 GPa were examined experimentally in diffusion couples formed around 22.5 (wt%) MgO, 17.5% Al2O3, and 60% SiO2. The diffusion matrix obtained from a simultaneous least squares inversion of convectively stable intersecting chemical diffusion profiles has large off-diagonal terms indicating, for example, very strong coupling of the flux of SiO2 with gradients in MgO. In contrast to an earlier report on multicomponent diffusion involving the same compositions studied here, we found no features along the stable diffusion profiles that could not be explained in terms of a 2 x 2 diffusion matrix. X-ray concentration maps of the sectioned diffusion charges showed that double-diffusive convection had occurred in a number of experiments along the direction of constant SiO2, even though the more dense melt had been placed below the less dense composition. The occurrence of such double-diffusive fingering instabilities is shown to be consistent with the predictions of linear stability theory.